Underpricing Saham pada Saat Initial Public Offering (IPO): Pengaruh Ukuran Perusahaan, Umur Perusahaan, Reputasi KAP dan Profitabilitas - Erly Mulyani; Rahmah Maulidya (Wahana Riset Akuntansi, 2021)
The phenomenon that often occurs when a company conducts an Initial Public Offering (IPO) is underpricing, which means that the stock price determination in the primary market is lower than the price of the same stock after being traded on the secondary market. This study examined the effect of  firm size, firm age, public accountant reputation and profitability of the underpricing. The population in this research are the companies that did the Initial Public Offering (IPO) in Indonesian Stock Exchange in the period of 2017-2020. The selection of the sample in this study using the purposive sampling method and retrieved 147 samples from 192 companies who are doing an initial public offering in BEI 2017-2020. This research use the multiple linear regression analysis. The results from t-test (partially) showed that public accountant reputation significantly effected on underpricing. While the firm size, firm age and profitability didn’t significantly effected the underpricing. The results from F-test (simultaneously) showed that firm size, firm age, public accountant reputation and profitability significantly effected the underpricing.  Keywords: Firm Age; Firm Size; Profitability; Public Accountant Reputation; Underpricing.